2011
DOI: 10.4161/cam.5.5.17723
|View full text |Cite
|
Sign up to set email alerts
|

Filopodia and adhesion in cancer cell motility

Abstract: Slender bundled actin containing plasma membrane protrusions, called filopodia, are important for many essential cellular processes like cell adhesion, migration, angiogenesis and the formation of cell-cell contacts. In migrating cells, filopodia are the pioneers at the leading edge which probe the environment for cues. Integrins are cell surface adhesion receptors critically implicated in cell migration and they are transported actively to filopodia tips by an unconventional myosin, myosin-X. Integrin mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
181
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(191 citation statements)
references
References 107 publications
9
181
1
Order By: Relevance
“…This allosteric binding site has thus the potential to guide the design of novel class-specific myosin inhibitors. In particular, myosin VI and myosin X are interesting pharmaceutical targets due to their recently established role in cell migration and metastasis (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…This allosteric binding site has thus the potential to guide the design of novel class-specific myosin inhibitors. In particular, myosin VI and myosin X are interesting pharmaceutical targets due to their recently established role in cell migration and metastasis (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that filopodia are sensors of chemotaxis. The filopodia projection detects changes in the environment and controls the direction of cell migration (Arjonen et al, 2011;Guiet et al, 2012). However, few studies have been published concerning the role of filopodia in OC differentiation and fusion.…”
Section: Introductionmentioning
confidence: 99%
“…The classical view of filopodia is that they act as antennae to probe the extracellular environment for guidance cues, matrix composition and the presence of other cells (Mattila and Lappalainen, 2008;Mellor, 2010;Arjonen et al, 2011). It is therefore assumed that filopodia mediate endothelial tip cell migration to guide vascular sprout formation and vascular patterning.…”
Section: Introductionmentioning
confidence: 99%